Kinematics of tectonic fracture development during regional folding in sandstones of the Kamlial Formation, Khushalgarh, northern Pakistan - Sayab, Mohammad; Jadoon, Qauid K. (Journal of Himalayan Earth Sciences, 2005)
Systematic relationships between the fracture orientation and fold geometry in sedimentary rocks have been used to explain the development of synfolding fractures. Based on field observations at the Khushalgarh syncline, located east of the Kohat plateau, we proposed that the orientation of fractures was influenced dominantly by two tectonic fracture sets, that is, the NE-SW and NW-SE. The NE-SW fracture set dominantly formed as mode I (tensile), whereas, the NW-SE fracture set developed as mode II (shear) conjugate fractures. The NE-SW trending fractures follow the axis of the syncline, whereas, the NW-SE fracture set crosscuts the fold axis. Most of the NESW fractures abut against the NW-SE fracture set. Based on the orientation and crosscutting relationships, their modes in response to stress, we conclude that the NESW trending fractures formed early than those of NW-SE fracture set. Though, both the fracture sets are formed during the folding, we suggest that they were not formed at the same time. Their crosscutting relationship suggests that they developed sequentially rather than synchronously. Our interpretations support the laboratory-based models where only one fracture orientation (or set of fractures with one orientation) form in response to single stress. However, as the stress distribution in folded strata changes over time, new fractures of distinct orientations can form during or late in the folding history. We conclude that the sandstone units underwent bedding-parallel extension during folding, where bedding is stretched to accommodate extension, parallel to the fold axis orientation. Bending of the ’limbs is a likely mechanism for the development of observed NE-SW trending fractures during folding, whereas the MV-SE fractures developed late in the folded history.